2014
DOI: 10.7314/apjcp.2014.15.5.2335
|View full text |Cite
|
Sign up to set email alerts
|

Development of Polymeric Nanopaclitaxel and Comparison with Free Paclitaxel for Effects on Cell Proliferation of MCF-7 and B16F0 Carcinoma Cells

Abstract: Paclitaxel is hydrophobic in nature and is recognized as a highly toxic anticancer drug, showing adverse effects in normal body sites. In this study, we developed a polymeric nano drug carrier for safe delivery of the paclitaxel to the cancer that releases the drug in a sustained manner and reduces side effects. N-isopropylacrylamide/ vinyl pyrrolidone (NIPAAm/VP) nanoparticles were synthesized by radical polymerization. Physicochemical characterization of the polymeric nanoparticles was conducted using dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…SEM analysis showed that paxlitaxel-loaded nanoparticles were like good solid balls. Multiple studies showed that many chemotherapeutics could inhibit the proliferation and induce cell apoptosis, such as paclitaxel (Yadav et al, 2014;Lim et al, 2015;Lin et al, 2015). By promoting microtubulin to form into canaliculus and suppressing depolymerization, paclitaxel-loaded drugs can lead to aberrant arrangement of microtubule fasolculus, formation of asteriform, abnormal function of spindle apparatus and inhibition of cell mitosis, thus inducing apoptosis and inhibiting cell proliferation (Pan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…SEM analysis showed that paxlitaxel-loaded nanoparticles were like good solid balls. Multiple studies showed that many chemotherapeutics could inhibit the proliferation and induce cell apoptosis, such as paclitaxel (Yadav et al, 2014;Lim et al, 2015;Lin et al, 2015). By promoting microtubulin to form into canaliculus and suppressing depolymerization, paclitaxel-loaded drugs can lead to aberrant arrangement of microtubule fasolculus, formation of asteriform, abnormal function of spindle apparatus and inhibition of cell mitosis, thus inducing apoptosis and inhibiting cell proliferation (Pan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer remains a significant problem for global health as it is one of the most common cause of tumorrelated death world-wide (Fouz et al, 2013;Engin et al, 2013;Sedighi et al, 2013;Zhu et al, 2013;Wu et al , 2014;Cabuk et al, 2014;Chin et al, 2014;Fouladi et al, 2014;Majeed et al, 2014;Gogia et al, 2014;Liu et al, 2014;Louisa et al, 2014;Moazzezy et al, 2014;Niu et al, 2014;Rizalar et al, 2014;Sipetic-Grujicic et al, 2014;Prajoko et al, 2014;Inanc et al, 2014;Varol et al, 2014;Yadav et al, 2014). Pemetrexed is a novel multitargeted antifolate that inhibits several enzymes in the de novo pathways of pyrimidine and purine biosynthesis, including thymidylate synthase, dihydrofolate reductase, and glycinamide ribonucleotide ormyltransferase.…”
Section: Discussionmentioning
confidence: 99%
“…Thus this effect makes drug loaded nano-carriers to concentrate in tumor sites (Maeda et al, 2000;Kingsley et al, 2006;Vicent and Duncan, 2006;Yadav et al, 2014). Among particulate drug carriers, polymeric nanoparticles exhibit suitable characteristics for encapsulation of many drugs (Torchilin, 2007).…”
Section: Introductionmentioning
confidence: 99%